The citizen formation in “Bogotá Humana” (2012-2014) within the national public policies in education - Caballero Dávila, Luis Felipe (Universidad Distrital Francisco José de Caldas, 2016)
The following article is a brief account of national educational policies from the 1980s to 2013 and the district ones between 2001 and 2011, making an analysis of the theoretical, political and economic approaches that underlie these policies, and a comparison between these and given approach from the educational policies of the “Bogotá Humana” between 2012 and 2014 in civic and political education approach.